Metabolic syndrome epidemic among Korean adults: Korean survey of Cardiometabolic Syndrome (2018). (October 2018) - Huh, Ji Hye; Kang, Dae Ryong; Jang, Ji-Yun; Shin, Jeong-Hun; Kim, Jang Young; Choi, Seonghoon; Cho, Eun Joo; Park, Jin-Sun; Sohn, Il Suk; Jo, Sang-Ho; Sung, Ki-Chul; Koh, Kwang Kon
Abstract: Background and aims: Little information exists on the prevalence of metabolic syndrome (MetS) in Korea since 2007. We aimed to provide up-to-date estimates of the prevalence of MetS and its trend in the general adult population in Korea. Methods: We compared the prevalence and pattern of MetS among participants in the Korean National Health and Nutrition Examination Surveys (KNHANES) IV (2007–2009), V (2010–2012), and VI (2013–2015), aged ≥19 years. Data from the 2005 census of the Korean population were presented according to age standardization. Results: The overall age-standardized prevalence of MetS in 2013–2015 was 20.3% (95% confidence interval [CI], 19.6%–21%). Since 2007, the overall prevalence of MetS has remained stable, whereas the prevalences among men and women, respectively, have increased and decreased slightly. By contrast, the prevalence of MetS among men aged 19–49 years has shown an increasing tendency since 2007. Moreover, nearly 40% of women aged ≥60 years had MetS in 2013–2015. Among the five components of MetS, only elevated fasting glucose level has shown an increasing trend since 2007 in both men and women. As the family income and educational level decreased, the prevalence of MetS increased. Conclusions: The overall prevalence of MetS has remained stable since 2007. However, the prevalence of MetS was higher in middle-aged men and women aged ≥60 years. Considering the close association between MetS and socioeconomic status, age- and sex-specific strategies should be developed at the national level for the treatment and prevention of MetS in Korea. Highlights: The prevalence of metabolic syndrome (MetS) in Korea has remained stable since 2007. The prevalence of MetS was higher in middle-aged men and women aged≥60 years. As the family income and educational level decreased, the prevalence of MetS increased.